Urinary Incontinence in Physically Active Young Women: Prevalence and Related Factors - Alves, Jessica Oliveira; Luz, Soraia Tonon Da; Brandão, Sofia; Da Luz, Clarissa Medeiros; Jorge, Renato Natal; Da Roza, Thuane (International Journal of Sports Medicine, 2017)
This cross-sectional survey aims to (1) verify the prevalence of urinary incontinence and its impact on the quality of life among nulliparous fit women, and to (2) analyze whether urinary incontinence is influenced by the intensity of the sport (high- vs. low-impact) or by the volume of physical activity (minutes per week) performed. Two hundred forty-five nulliparous women (18–40 years) completed the International Consultation on Incontinence Questionnaire-Short Form, the Kings Health Questionnaire and a questionnaire regarding demographic and training variables. Overall 22.9% of the participants self-reported urinary incontinence, and among them, 60.7% had stress urinary incontinence. Incontinent women demonstrated worse quality of life than continent females (p=0.000). Women practicing high-impact sports presented higher frequency in loss of urine than those practicing low-impact sports (p=0.004). Regardless the intensity of the sport, the volume of exercise showed positive association with the frequency of loss of urine (p=0.005, r=0.475). In conclusion, almost one fourth of the women enrolled in this study reported symptoms of urinary incontinence and worse quality of life than those who were continent. Women who practice high-impact sports or who have higher volume of training should be aware of the symptoms associated with pelvic floor dysfunction, since they seem to predispose to urine leakage.
Keywords: pelvic floor muscles; sports; urinary incontinence; risk factors; prevalence; quality of life